2020
DOI: 10.1002/nop2.516
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep quality during chemotherapy: An integrative review

Abstract: Aim To identify the most important factors associated with sleep pattern changes in patients with cancer during chemotherapy treatment. Design An integrative review of the literature was performed between December 2017–August 2018. Methods Two independent reviewers searching the National Library of Medicine (PubMed/MEDLINE), Cumulative Index of Nursing and Allied Health Literature (CINAHL) and Latin American and Caribbean Literature in Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…The efficacy of treatments might be affected by the precipitating or perpetuating factors of chemotherapy-associated insomnia [ 7 , 8 ]. Acupuncture has been reported to generate an 8.3-point reduction in ISI score among cancer survivors who have completed active treatments [ 33 ], and about 6-point reduction among breast cancer patients undergo or post-chemotherapy in our present and previous trial [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of treatments might be affected by the precipitating or perpetuating factors of chemotherapy-associated insomnia [ 7 , 8 ]. Acupuncture has been reported to generate an 8.3-point reduction in ISI score among cancer survivors who have completed active treatments [ 33 ], and about 6-point reduction among breast cancer patients undergo or post-chemotherapy in our present and previous trial [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients described a cyclical loop where lack of sleep caused more fatigue, which prevented them from walking for exercise. Sleep quality in cancer dependents on multiple parameters such as fatigue, pain, depression, anxiety and distress 19 and so is hard to interpret. Nevertheless, a recent systematic review showed that improving sleep quality eased the symptoms of cancer-related fatigue although was unable to determine if sleep quality improvement was the sole factor behind fatigue lessening.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relatively strong body of evidence exists to support the role of the microbiota, and indeed SCFAs in modulating the toxicities described above, emerging data is now beginning to suggest a possible role in psychoneurological symptoms. This cluster of related symptoms includes cognitive impairments affecting memory, executive function, processing speeds, and learning [ 110 , 111 , 112 ], as well as psychological elements including depression/anxiety, fear of recurrence, and personality changes [ 113 , 114 ]. Although the current evidence is limited, this mechanism is supported by: i) changes in the gut microbiota that coincide with psychoneurological symptoms in people with cancer, and ii) direct involvement of SCFAs in other neurological conditions that share similar symptom profiles.…”
Section: Scfas and Cancer Treatment Toxicitiesmentioning
confidence: 99%